Active Strategy of Avoiding Resonance - Hojnicki-Szulc, J. (Engineering Transactions, 1989)
The problem of active control of natural frequencies by changes of local stiffness in structural elements in order to avoid resonance (due to variable frequency of excitation) is considered, The optimal strategy of play with switchable control parameters in the case of a simple discrete structure and continuous beam cantilever is discussed. lt is concluded that even one structural element with a controllable stiffness coefficient gives us an efficient (in most cases) device to avoid resonance frequencies in the structure under variable excitation.